Legal Provisions and Practical Effects of Burden of Proof in Online Copyright Infringement Cases Under China’s Copyright Law - Haonan Zhang (Law and Economy, 2024)
This paper explores the legal provisions and practical effects of the burden of proof in online copyright infringement cases under China’s Copyright Law. With the rapid growth of digital technology and the increasing prevalence of online platforms, copyright infringement has become a significant challenge in China. The paper examines the specific rules set forth in the Copyright Law, particularly those that allow for a shift in the burden of proof upon the presentation of preliminary evidence by the copyright holder. It analyzes the impact of these provisions on both plaintiffs and defendants, highlighting the benefits of empowering copyright holders and the challenges associated with procedural fairness, evidentiary standards, and judicial consistency. The paper also discusses the evolving use of digital evidence, such as blockchain technology, and the need for clearer guidelines to balance the rights of all parties. Ultimately, it argues for continued refinement of the legal framework to ensure effective and equitable copyright enforcement in the digital age.